Influence of curing temperature and stress conditions on mechanical properties of cementing paste backfill - Walske, Megan; McWilliam, H.; Doherty, J.; Fourie, A. (2015)
© 2015, National Research Council of Canada. All rights reserved. Cemented paste backfill (CPB) has been observed to achieve greater cemented strength when cured in situ compared with equivalent mixes cured and tested in a laboratory environment. This is in part due to the development of effective stress and generation of elevated temperatures by exothermic cement hydration reactions occurring during curing in a typical underground stope environment. This differs from curing in typical laboratory environments, where little or no effective stresses are generated and curing occurs under constant-temperature conditions. This paper outlines the development, calibration, and testing of a temperature-controlled hydration cell that provides closer representation of in situ conditions by controlling the rate and final amount of specimen temperature increase, in addition to curing under effective stress. The temperature-controlled hydration cell was used to examine the effect of curing under combined effective stress and temperature conditions on the development of small-strain stiffness over a 7 day curing period and the unconfined compressive strength at the end of this period. Curing with both elevated temperature and effective stress was found to significantly increase the mechanical properties of CPB compared with curing at elevated effective stress or ambient temperatures alone.